Suchon, Gabrielle [1693]. Tratado sobre la debilidad, la ligereza y la inconstancia que sin fundamento se atribuye a las mujeres. Edición de María Luisa Guerrero. Salamanca, Guillermo Escolar Editor, Colección Hitos, 2020. ISBN: 978-8418093-17-3. 136 páginas. - Antia, Maider Andreano (Investigaciones Feministas, 2024)
Review of the work "A treaty on weakness, lightness and inconstancy that without foundation is attributed to women" written by philosopher and writer Gabrielle Suchon in 1693 and edited by María Luisa Guerrero (2020). After an analysis by the latter on the context, the author and the introduction of the subject of the Women's Quarrel, Guerrero presents the work translated into Spanish. In the treaty, In the treaty, Suchon counterarguments the topics by which many of the men inserted in the debate of the Women's Quarrel considered women of a weak, light and fickle nature.